Historical review of the fiscal system (s.n., 1851)
Contains section XXVII(2nd part)-XXIX, continued from tract no. 34. - Issued by the Liverpool Financial Reform Association. - Authorship claimed by Alexander Somerville. - In pamphlet volume with covertitle: Tracts of the Liverpool Financial Reform Association.